Effect of microstructure on hydrogen permeation and trapping in natural gas pipeline steels - Aminul Islam; Qidong Li; Emma Storimans; Kay Ton; Tahrim Alam; Zoheir N. Farhat (npj Materials Degradation)
Abstract This study examines hydrogen permeation and trapping in three types of natural gas pipeline steels from different decades in Canada—modern, vintage, and legacy steels. Electrochemical permeation experiments were conducted to measure the diffusion coefficient, subsurface concentration, and trap density of hydrogen. The results were analyzed to evaluate the susceptibility of these steels to hydrogen embrittlement and to understand the effects of hydrogen on their mechanical properties. Vintage steel exhibited 50% higher steady-state permeation current and 97% greater effective diffusivity compared to modern steel, while legacy steel showed intermediate values. Hydrogen diffusion increased with grain size and pearlite content but decreased with dislocation density. Modern steel demonstrated the highest resistance to hydrogen permeation due to its finer grain structure and higher dislocation density. This study provides essential insights into the diffusion behavior and trapping mechanisms of hydrogen in natural gas pipeline steels, enhancing the understanding of material performance under hydrogen exposure.